Implementation Of Observation Of Managerial Supervision Of A Vocational High School In The City Of Padang - Mahzuardi Mahzuardi; La Ode Alwin Syahputra; Ambiyar (Institute of Computer Science (IOCS), 2022)
This paper aims to find out information on how managerial supervision at state vocational high school 6 is implemented according to the needs of the school, precisely on Tuesday 8 March 2022, from the results of these observations, data on managerial supervision that has been carried out, based on these observations include SMKN 6 Padang has carry out various needs from the many aspects of the component around 83 types, means of managerial supervision as a step in managing school administration that functions as a supporter of the implementation of learning, and aims to create relevant education.